2015
DOI: 10.1016/j.pnsc.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ductility of Mg–3Al–1Zn alloy reinforced with short length multi-walled carbon nanotubes using a powder metallurgy method

Abstract: Mg-3Al-1Zn-CNTs composites, with different weight fractions (0.25-1.0 wt%) of carbon nanotubes (CNTs) were successfully fabricated via a powder metallurgy method. The processing parameters were adopted in such a way to have uniform dispersion of short length CNTs without any damage, as well as refined and dissolved β phases structures throughout the composite matrix. The composite exhibited impressive increase in microhardness (about þ23%) and tensile failure strain value (about þ98%) without significant compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The initial volume fraction of incorporated CNTs, formation of intermetallics, and quality of the formed interface between the Mg and nanotubes are the important factors in determining the mechanical properties of the nanocomposites. It is shown that an increase in the initial amount of incorporated CNTs may promote the refinement of coarse grains and enhance the failure strain [146,147]. Figure 22 shows the evolved microstructure of CNT-AZ31 nanocomposites produced using the disintegrated melt deposition technique followed by hot extrusion.…”
Section: (C) Cnt-reinforced Mg Matrix Nanocompositesmentioning
confidence: 99%
See 3 more Smart Citations
“…The initial volume fraction of incorporated CNTs, formation of intermetallics, and quality of the formed interface between the Mg and nanotubes are the important factors in determining the mechanical properties of the nanocomposites. It is shown that an increase in the initial amount of incorporated CNTs may promote the refinement of coarse grains and enhance the failure strain [146,147]. Figure 22 shows the evolved microstructure of CNT-AZ31 nanocomposites produced using the disintegrated melt deposition technique followed by hot extrusion.…”
Section: (C) Cnt-reinforced Mg Matrix Nanocompositesmentioning
confidence: 99%
“…The formation of a clean interface with no impurity or defect is shown to improve the mechanical properties [144]. A recent study by Rashad et al [146] showed that the formed intermetallics in MWNTs-dispersed Mg-3Al-1Zn alloys are refined with the CNTs inclusion. Figure 23 indicates the schematic demonstration of Mg17Al12 generation at the interface of Mg-3Al- Similar to CNT-Al and CNT-Ti binary systems, the precipitation of the mentioned intermetallics may bilaterally affect the mechanical properties of CNT-dispersed Mg matrix nanocomposites.…”
Section: (C) Cnt-reinforced Mg Matrix Nanocompositesmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14][15]. Graphene incorporation into aluminum matrix reports in enhancement of hardness, and tensile strength [16][17][18][19][20]. Graphene nanoplatelets (GNPs) are known to be multilayer Graphene.…”
Section: Introductionmentioning
confidence: 99%